PENERAPAN LEAN MANUFACTURING DENGAN VALUE STREAM MAPPING DAN KAIZEN 5W 2H GUNA MENGURANGI WASTE DAN CYCLE TIME PROSES ASSY PANEL RANGKA PADA PT. XYZ - Muhammad Julian Syaputra; Donny Setiawan; Yan Kurnia Hadi (LPPM Universitas Pramita Indonesia, 2023)
Abstract Current developments in the industry spur companies to increase their productivity levels. Especially in manufacturing companies that are asked to continuously improve their production. Both in terms of quality, quantity, price, and in other aspects. The company that is the object of research is a company engaged in automotive production. Problems faced by PT. XYZ is not achieving the production target of pcs/hour so that it disrupts the delivery part process to the Customer. This is due to the long production time and the amount of waste that occurs on the production floor. If this problem is not immediately resolved, it will cause losses to the company. The research objective is to identify waste that occurs on the production floor and make repairs on the production floor by reducing waste based on the Lean Manufactuing approach. The method used is Value Stream Mapping and Kaizen 5W 2H. The results of identification and measurement after improvement, obtained a significant reduction of VA time and NVA time, namely VA time of 35.07 seconds (40.2%) and NVA time of 52.17 seconds (59.8%), with a total time of 87.24 seconds. And the decrease in Cycle Time by 26.57 seconds against the Frame Assy Panel process, there is an increase in productivity (pcs / hour). Keywords: VSM, Kaizen, Lean Manufactuing